Concurrent exercise training during pregnancy is related to more favourable maternal lipid levels when IL-8 increases - Acosta-Manzano, P.; Flor-Alemany, M.; Van Poppel, M. N. M.; Coll-Risco, I.; Segura-Jiménez, V.; Stanford, K. I.; Aparicio, V. A. (Journal of Sports Sciences, 2025)
It is unclear how exercise-induced stimuli affect and translate into immunometabolic adaptations during pregnancy. We previously found that exercise influences maternal-foetal circulating cytokines (IL-1ß, IL-6, IL-8, IL-10, TNF-a). This study investigated i) the influence of an exercise training programme during pregnancy on metabolic markers (glycaemic and lipid markers, and C-reactive protein) in maternal, and cord arterial and venous serum; and ii) whether these cytokines mediated the effects of exercise on metabolic markers. Eighty-eight pregnant women, divided into exercise (n = 44) and control (n = 44) groups, participated in this quasi-experimental study. The exercise group followed a 60-min 3 days/week concurrent (aerobic+resistance) exercise training. Glycaemic and lipid markers and C-reactive protein concentrations, and cytokines levels, were measured at weeks 17 and 34 and birth with standard biochemical methods and Luminex xMAP technology. Overall, exercise did not induce detectable changes in maternal metabolic markers during pregnancy, except for those exercisers whose IL-8 levels increased, where it was related to lower maternal total cholesterol (indirect effect= -9.1; 95% CI= -24.6, -1.1) and low-density lipoprotein-cholesterol gains (-8.9; -21.9, -1.1). This suggests a mechanism by which exercise may optimise lipid metabolism regulation. Moreover, exercise was related to lower cord arterial serum glucose levels. Further research, especially concerning foetal metabolism, is necessary.